Nonadhesive acoustic membranes based on polyimide - Vorob'ev, A. V.; Zhora, V. D.; Baklaev, K. K.; Grunyanskaya, V. P. (Technology and design in electronic equipment, 2014)
The paper presents a comparison of technical characteristics of acoustic membranes with an adhesive layer and nonadhesive membranes. The authors present the manufacturing technology for acoustic membranes based on aluminum-polyimide film dielectrics and analyze the advantages of such membranes in comparison to other sound emitters.